2013
DOI: 10.1007/s10457-013-9615-z
|View full text |Cite
|
Sign up to set email alerts
|

Seedling growth and water relations of three Cedrela species sourced from five provenances: response to simulated rainfall reductions

Abstract: The effects of different simulated rainfall regimes on water relations, growth, and biomass production and allocation of five provenances of Cedrela fissilis, C. saltensis and C. balansae were assessed in a pot-grown seedling experiment in greenhouse under uncontrolled conditions. Four simulated rainfall regimes were applied: 600 mm year -1 (severe water deficit), 800 mm year -1 (mild water deficit), 1,000 mm year -1 (mild wet), and 1,200 mm year -1 (well-watered) used as control. Provenances were compared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
(28 reference statements)
0
6
1
Order By: Relevance
“…It indicated that Prince Rupprecht's larch is more affected by water deficit than eastern larch, and white birch is more affected than paper birch. The result conflicts with our second hypothesis, as well as the conclusions of Otieno et al (2005) and Ruiz et al (2013).…”
Section: Site-specific Responsecontrasting
confidence: 99%
See 3 more Smart Citations
“…It indicated that Prince Rupprecht's larch is more affected by water deficit than eastern larch, and white birch is more affected than paper birch. The result conflicts with our second hypothesis, as well as the conclusions of Otieno et al (2005) and Ruiz et al (2013).…”
Section: Site-specific Responsecontrasting
confidence: 99%
“…The morphological changes of the four species to drought were consistent with the general responses of other species. Leaf shedding of birch seedlings in low-water environments has * difference at P < 0.05, ** difference at P < 0.01 been shown to occur to limit evaporative losses when seedlings can no longer maintain a positive carbon balance (Levesque et al 2013;Ruiz et al 2013;Mantovani et al 2014). During drier periods, reduction in available soil water results in closure of stomata and decrease of stomatal conductance C i to limit evaporative losses.…”
Section: Seedling General Responsementioning
confidence: 99%
See 2 more Smart Citations
“…This shows that identifying the trigger factor for growth rhythms in tropical trees is not always straightforward, as different tropical tree species respond to different cues (Borchert et al 2015), and there could also be differences in response between sub-populations of the same species (e.g. Ruiz et al 2013;Stubblebine et al 1978).…”
Section: Introductionmentioning
confidence: 99%